NLA Høgskolen Fagutvikling og sjølvforståing på kristen grunn - Hagesæther, Gunhild; Innerdal, Gunnar; Kvam, Bjarne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
NLA University College celebrated their 50-year jubilee in the 2018. As a part of the occation they hosted a seminar which in turn produced many of the contributions in this antology. This book seeks to discuss the place of the institution, a private, christian college, in the Norwegian higher education structure.